2014
DOI: 10.1111/are.12547
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different dietary lipid sources on tissue fatty acid composition, serum biochemical parameters and fatty acid synthase of juvenile mud crabScylla paramamosain(Estampador 1949)

Abstract: A 6‐week study was conducted to determine the effects of different lipid sources in pelleted diets on juvenile mud crab Scylla paramamosain. Five isonitrogenous and isolipidic diets containing 8% level of fish oil (FO), lard (LD), safflower oil (SO), perilla seed oil (PO) or mixture oil (MO; VFO:VSO:VPO = 1:1:1), and a live food of marine bivalve Potamocorbula rubromuscula as the control diet (CF), were fed to groups of 25 juvenile crabs (average initial weight 7.4 g, carapace width 3.5 cm) in triplicate. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…However, our results showed that the serum GLU of Jian carp was not influenced by the experimental diets. Zhao et al () reported no significant differences in the serum Chol and TG levels of mud crabs between the safflower oil group (rich in LA) and the perilla seed oil group (rich in LNA), corresponding to our results.…”
Section: Discussionsupporting
confidence: 88%
“…However, our results showed that the serum GLU of Jian carp was not influenced by the experimental diets. Zhao et al () reported no significant differences in the serum Chol and TG levels of mud crabs between the safflower oil group (rich in LA) and the perilla seed oil group (rich in LNA), corresponding to our results.…”
Section: Discussionsupporting
confidence: 88%
“…We show that blunt snout bream fed the CO diet had the highest levels of FAS and ACC activities and the highest FAS expression, indicating that high levels of dietary SFA increase the activity and mRNA expression of FAS. Similarly, Zhao, Wen, Li, Zhu, and Li () reported that compared to saturated fatty acids, polyunsaturated fatty acids have a stronger inhibitory effect on FAS activity. CPT I and CPT II are considered to be the key regulatory enzymes in mitochondrial β‐oxidation (Kerner & Hoppel, ).…”
Section: Discussionmentioning
confidence: 89%
“…In 2018, the yield of farmed mud crabs (mainly S. paramamosain) reached 157 712 tons (19) . However, the development of commercial feed for S. paramamosain has lagged in the crab farming industry, and there are few reports on the nutritional requirements of mud crab (20)(21)(22)(23) , although dietary lipid levels of 8•52-11•63 % (optimum 9•50 %) could maintain growth performance (20) . The requirement for dietary LC-PUFA in swimming crab was supposed to range from 6•0 to 23•6 mg/g of diets (7,8,10,11) , and the optimum dietary DHA: EPA ratio for juvenile crab was about 1•0.…”
mentioning
confidence: 99%